Unraveling the potential of bacteria isolated from the equatorial region of Indian Ocean in mercury detoxification - Gajendra Joshi; Pankaj Verma; Balakrishnan Meena; Prasun Goswami; D Magesh Peter; Dilip Kumar Jha; Nambali Valsalan Vinithkumar; Gopal Dharani (Frontiers in Marine Science, 2022)
The marine environment is most vital and flexible with continual variations in salinity, temperature, and pressure. As a result, bacteria living in such an environment maintain the adaption mechanisms that are inherent in unstable environmental conditions. The harboring of metal-resistant genes in marine bacteria contributes to their effectiveness in metal remediation relative to their terrestrial counterparts. A total of four mercury-resistant bacteria (MRB) i.e. NIOT-EQR_J7 (Alcanivorax xenomutans); NIOT-EQR_J248 and NIOT-EQR_J251 (Halomonas sp.); and NIOT-EQR_J258 (Marinobacter hydrocarbonoclasticus) were isolated from the equatorial region of the Indian Ocean (ERIO) and identified by analyzing the 16S rDNA sequence. The MRBs can reduce up to 70% of Hg(II). The mercuric reductase (merA) gene was amplified and the mercury (Hg) volatilization was confirmed by the X-ray film method. The outcomes obtained from ICP-MS validated that the Halomonas sp. NIOT-EQR_J251 was more proficient in removing the Hg from culture media than other isolates. Fourier transform infrared (FT-IR) spectroscopy results revealed alteration in several functional groups attributing to the Hg tolerance and reduction. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis confirmed that strain Halomonas sp. (NIOT-EQR_J248 and NIOT-EQR_J251) released Isooctyl thioglycolate (IOTG) compound under mercury stress. The molecular docking results suggested that IOTG can efficiently bind with the glutathione S-transferase (GST) enzyme. A pathway has been hypothesized based on the GC-MS metabolic profile and molecular docking results, suggesting that the compound IOTG may mediate mercuric reduction via merA-GST related detoxification pathway.